2020
DOI: 10.17660/actahortic.2020.1268.36
|View full text |Cite
|
Sign up to set email alerts
|

The influence of 20% white shade nets on fruit quality of ‘Nadorcott’ mandarin

Abstract: The external and internal quality of citrus fruit determines consumer acceptance, thereby driving the consumption and demand for fresh fruit. Emphasis is placed on producing a high volume of fruit of good quality, and it is known that light intensity is especially important in influencing sugar content, rind color, and blemish incidence. Extreme environmental conditions are challenging controllable factors. Therefore shade netting is used especially on fruit crops for protection against dramatic climatic event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…To mitigate these variations between the different canopy positions, the implementation of shading nets could be an effective solution. As reported by Lee et al (2015) and later confirmed by Cronjéet al (2020), the use of white shade nets in 'Ponkan' mandarin farms produced a significant reduction in fruit surface temperature and sunburn, higher juice percentage, and lower weight loss and decay than in non-shaded fruit while postharvest peel colour, TSS and TA were unaffected. Therefore, the use of shading nets could decrease the variability in temperature, sunlight exposure, and transpiration of the different canopy positions and, as a result, improve the consistency in fruit quality at harvest.…”
Section: The Effect Of Harvest Time and Canopy Position On The Postha...supporting
confidence: 52%
“…To mitigate these variations between the different canopy positions, the implementation of shading nets could be an effective solution. As reported by Lee et al (2015) and later confirmed by Cronjéet al (2020), the use of white shade nets in 'Ponkan' mandarin farms produced a significant reduction in fruit surface temperature and sunburn, higher juice percentage, and lower weight loss and decay than in non-shaded fruit while postharvest peel colour, TSS and TA were unaffected. Therefore, the use of shading nets could decrease the variability in temperature, sunlight exposure, and transpiration of the different canopy positions and, as a result, improve the consistency in fruit quality at harvest.…”
Section: The Effect Of Harvest Time and Canopy Position On The Postha...supporting
confidence: 52%